Associations of physical activity with the risks of osteoarthritis and subtypes: a population-based cohort study of UK Biobank data - Huijie Gu; Rong Chen; Tingting Fang; Jun Xu; Yiming Zhang; Chong Bian; Xiangyang Cheng; Xiaofan Yin; Chuhuai Wang; Guangnan Chen (Bone & Joint Research, 2025)
Aims: This study aimed to investigate the relationship between physical activity (PA) and the risk of osteoarthritis (OA) and its subtypes. Methods: We included participants from the UK Biobank aged 37 to 73 years from February 2006 to June 2010. Baseline PA levels were categorized as high (≥ 3,000 metabolic equivalent of task (MET)-min/week), moderate (600 to < 3,000 MET-min/week), or low PA (< 600 MET-min/week) based on current public health guidelines. The associations between PA and OA and its main subtypes (hand, hip, and knee OA) were analyzed using Cox-proportional hazard models. The mediating role of BMI was tested under a causal counterfactual framework. Results: The median follow-up period was 12.50 years, with 25,036 incident total OA cases. Compared to low PA, we found no significant association between moderate PA and total OA risk. However, high PA significantly increased the risk of total OA by 19% (hazard ratio (HR) 1.19, 95% CI 1.15 to 1.23). This result is consistent with knee OA and hip OA, where HR was 1.25 (95% CI 1.19 to 1.31) for knee OA risk and 1.17 (95% CI 1.10 to 1.24) for hip OA risk, respectively. Moderate PA was associated with 14% (HR 0.86, 95% CI 0.76 to 0.97) reduction in the risk of hand OA. Moreover, we found that BMI mediated the association between PA and OA risk, with the mediating proportion for total OA, hand OA, knee OA, and hip OA, at 75.48%, 2.42%, 10.20%, and 51.39%, respectively. Conclusion: These findings suggest that high levels of PA increased the risk of total OA, as well as knee and hip OA, while moderate levels of PA significantly mitigate the risk of hand OA. BMI appears to mediate the relationship between PA and OA risk. Future research should elucidate the underlying mechanisms. Cite this article: Bone Joint Res 2025;14(7):656–665.